A Rare Case of a Bleeding Ampullary Dieulafoy Lesion: Technical Challenges in Achieving Haemostasis - Thio, Joel; Taylor, Aidan; Smith, Nicholas; Gururatsakul, Montri (International Journal of Innovative Research in Medical Science, 2025)
We present a rare case of a bleeding ampullary Dieulafoy lesion with technical difficulties in management, starting with a standard forward-viewing gastroscope, subsequent use of a side-viewing duodenoscope, and eventually endoscopic retrograde cholangiopancreatography (ERCP) and biliary stenting to allow for safe haemostasis with argon plasma coagulation (APC). A 56-year-old male was admitted with pneumonia and fluid overload in the context of end-stage renal disease from poorly controlled diabetes mellitus and hypertensive nephrosclerosis on regular haemodialysis. He was on dual anti-platelet therapy with aspirin and ticagrelor for recent cardiac stenting. Five days into his admission he was noted to have melena with a haemoglobin drop from 87 g/L to 56 g/L, with a urea rise of 23.9 mmol/L from a baseline of 11.0 mmol/L. Subsequent gastroscopy revealed active bleeding from the major ampulla without any underlying ulcer or tumour, superior to the biliary orifice, consistent with an ampullary Dieulafoy lesion. The duodenoscope was then introduced for a better view and access to the major ampulla. APC was attempted at 0.8 L/min at 30 Watts due to the size and location, but haemostasis was unsuccessful. The decision was made to proceed to ERCP and biliary stenting to prevent complications from heat injury to the bile duct and possible pancreatitis. A 7Fr by 4cm double pigtail biliary plastic stent was placed into the common bile duct. APC was re-applied at 0.8 L/min at 30 Watts at the bleeding spot with successful haemostasis. This case report aims to highlight the rare occurrence of duodenal ampullary Dieulafoy lesions and the need for prompt recognition and use of resources such as side-view duodenoscopy and ERCP for safe therapeutic management.